Profil Kemampuan Pemecahan Masalah Matematis Siswa dalam Menyelesaikan Soal Matriks ditinjau dari Perbedaan Gender di Kelas XI SMA Negeri 01 Menjalin - Yani, Yani; Hartono, Hartono; Abdillah, Abdillah (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this study is to find out the characteristics and evaluate students' mathematical problem-solving abilities when solving matrix problems, with a special focus on the gender gap. This study uses a qualitative research approach using a descriptive methodology. The research was carried out at SMA Negeri 01 Menjalin with a sample of 21 students consisting of 14 women and 7 boys. The analysis focused on two students of each gender. The data collection tools used are tests, interview guidelines, validation sheets, and documentation. The data collection techniques used in the study are measurement techniques and direct communication techniques. Meanwhile, the data analysis technique is by reducing data, presenting data, and drawing conclusions. Based on the results of data analysis, it is known that each gender has different problem-solving skills. The average score of men's problem-solving ability was 45.71 based on the number of samples of 7 students. For women, the average score was 73.57, based on a sample of 14 students. It is proven that women have superior problem-solving skills than men